LINGUODIDACTIC INTERPRETATION OF THE CONCEPT OF BILINGUAL COMPETENCE AND ITS INTEGRATION WITH THE CLIL APPROACH (Universal International Scientific Journal, 2026)
This article analyzes the linguodidactic essence of the concept of bilingualcompetence, its structural components, and the peculiarities of its formation. It also provides ascientific substantiation of the role and significance of the CLIL (Content and Language IntegratedLearning) approach in the development of this competence. The possibilities for developing students’communicative and cognitive competences through the integration of language and subject contentbased on the CLIL approach are highlighted.
Keywords: bilingual competence; linguodidactics; CLIL